STRATEGI PENULISAN ARTIKEL DALAM BAHASA INGGRIS: CIRI-CIRI STRUKTURAL DAN LEKSIKAL DALAM BAGIAN PENDAHULUAN - * Mirahayuni (Universitas 17 Agustus 1945 Surabaya, 2013)
ABSTRACT. This article focuses on identifying strategies of writing research report articles in English. Specifically it focuses on strategies of writing the Introduction Section of report. It examines the lexical and structural features of the section. This descriptive qualitative study involves 20 internationally published research articles written by native English speakers. The results of the study show that research report articles in English are conventionally organized and structured to meet their purpose of the writing and distinctive writing practices in the particular academic communication and culture. The implication of the findings is that non-native English writers need to be aware of the writing practices and write their research report articles in English accordingly.Â Keywords:Â English academic writing, textual and structural strategies